A playful production process : for game designers (and everyone) - Lemarchand, Richard, ....- (Cambridge (Mass.) : MIT press, 2021)
This book teaches game designers, aspiring game developers, and game design students how to take a digital game project from start to finish—from conceptualizing and designing to building, playtesting, and iterating—while avoiding the uncontrolled overwork known among developers as “crunch.” Written by a legendary game designer, A Playful Production Process outlines a process that connects the creative aspects of game design with proven techniques for effective project management. The book outlines four project phases—ideation, preproduction, full production, and post-production—that give designers and developers the milestones they need to advance from the first glimmerings of an idea to a finished game.
Keywords: Game design